Farmers markets as facilitators of eco-habitus - Barnhardt, KM, author; Hastings, Orestes P., advisor; Carolan, Michael, committee member; Mueller, Megan, committee member (Colorado State University. Libraries, 2024)
In this study, I seek to resituate eco-habitus into Pierre Bourdieu's understanding of the field to show how farmers markets can structure themselves as facilitators of spaces where all individuals, specifically those with low economic and cultural capital, can enact their eco-habitus. To ask how farmers markets can achieve this, I explore what predictors lead to a market accepting the United States Department of Agriculture's, Food and Nutrition Services, Nutrition Programs (NP), as forms of payment, the presence of nutrition and health programs, and food donation and conservation programs. I also provide a breakdown of the types of programming markets provide. To examine, this I conducted an original national survey of farmers market managers (N=473). I combined this with data from the American Community, County Presidential Election Returns, and the US Census. Logistic regression results indicate more liberal counties have a higher probability of accepting NP and having food donation programs, while more urban counties have a higher probability of having nutrition programming. Markets in more affluent counties are less likely to accept NP, while urban counties with higher percentages of people of color, and low-income individuals, suggest these individuals still possess eco-habitus but might be pulling from non-dominate ethical repertories commonly associated with eco-habitus. This study offers a critique of farmers market and who has access to them, contributes to the growing literature on eco-habitus, and attempts to resituate eco-habitus into Bourdieu's understanding of field. It also provides a national survey of farmers market managers.
Keywords: farmers' market managers; federal nutrition programs; USDA; farmers' markets; eco-habitus; Pierre Bourdieu